IMPLEMENTASI BIG DATA ANALYSTICS DALAM PRAKTIK AUDIT PADA PERUSAHAAN: LITERATURE REVIEW - Sayidah Maryam Sinosi; Refor Moerdianto; Grace T. Pontoh; Mediaty Mediaty (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the benefits of implementing big data analytics in auditing practices in companies. The design of this research is Sistematic Literature Review (SLR) uses a narrative method. The results show that through its capabilities, big data can maximize the forensic audit function to detect fraud. This can then be an answer to overcome agency problems that arise due to fraud. It is known that one of the factors that hinders auditors from detecting fraud is that the auditors have limitations in analyzing various unstructured data and non-financial data (such as contract details, meeting results, news related to management, and so on). This problem can be overcome by auditors by utilizing big data, through the function of data analytics tools.